Quantifying Resource and Energy Losses from Waste Fires in Poland: A Barrier to Circular Economy Transition - Katarzyna Grzesik; Magdalena Zabochnicka; Robert Oleniacz; Ryszard Kozakiewicz (Energies)
Waste fires are significant sources of atmospheric pollutants that contribute to environmental degradation and public health risks. They also lead to considerable losses in recyclable materials and energy. In Poland, waste fire incidents have increased in recent years, peaking in 2018–2019. This study quantifies the volume and mass of waste burned and assesses the associated losses in material and energy potential. A detailed incident inventory was compiled, including waste types and burned volumes, which were converted to mass values. This study estimates the potential fate of this waste under proper waste management scenarios. Recyclable materials, such as plastics, metals, paper, textiles, and rubber, are permanently removed from circulation, increasing the reliance on virgin resources. Energy losses were calculated using the lower heating values of each waste type, assuming a full energy recovery potential. In 2018, large and very large fires resulted in an estimated 170,000–1,016,640 m3 of burned waste, with corresponding energy losses of 495–2970 TJ. In 2019, estimates ranged from 68,000–410,000 m3 and 139–831 TJ. Plastics, refuse-derived fuel (RDF), and tires accounted for the majority of these losses. These findings highlight the relevance of waste fires in undermining recycling or energy recovery efforts and slowing progress toward a circular economy.